Pharmacy students’ perception and inclination toward scholarly research publications: A multinational study - Bhagavathula, Akshaya Srikanth; Bandari, Deepak Kumar; Jamshed, Shazia Qasim; Chattu, Vijay Kumar (Wolters Kluwer Medknow, 2018)
BACKGROUND: Scholarly research experiences during student life can make pharmacy students capable of reaching the pinnacle of triumph with scientific skills.AIM: The aim of this study is to assess the perception of pharmacy students and their inclination toward scholarly research publications.MATERIALS AND METHODS: A cross‑sectional web‑based survey was conducted among pharmacy students across India, Malaysia, and Pakistan. A 21‑item questionnaire was distributed through different social networking sites between July and September 2016. Descriptive and Chi‑square tests were used to analyze the findings. A value of P < 0.05 was considered as statistically significant.RESULTS: Of 543 pharmacy students approached, 348 participants from India, Pakistan, and Malaysia were included giving a response rate of 64%. The study comprises 48.5% of males and 51.4% of females, studying a bachelor of pharmacy (44.5%), and from private institutions (94%). Nearly, three‑fourths (76.4%) of the students had no publications but showed high interest toward original research (87.4%). Most of the participants cited the reasons to engage in the scholarly publication is too advanced research/share findings (74.1%), and to improve writing and research skills (73.6%). Further, a significant percentage of students agreed that contributing to the literature during student life as a valuable experience and publishing will provide them with personal fulfillment.